Am I the odd one? Exploring (in)congruencies in the realism of avatars and virtual others in virtual reality - Mal, David; Döllinger, Nina; Wolf, Erik; Wenninger, Stephan; Botsch, Mario; Wienrich, Carolin; Latoschik, Marc Erich (Frontiers in Virtual Reality, 2024)
Virtual humans play a pivotal role in social virtual environments, shaping users' VR experiences.The diversity in available options and users' individual preferences can result in a heterogeneous mix of appearances among a group of virtual humans. The resulting variety in higher-order anthropomorphic and realistic cues introduces multiple (in)congruencies, eventually impacting the plausibility of the experience. However, related work investigating the effects of being co-located with multiple virtual humans of different appearances remains limited. In this work, we consider the impact of (in)congruencies in the realism of a group of virtual humans, including co-located others (agents) and one's self-representation (self-avatar), on users' individual VR experiences. In a 2 × 3 mixed design, participants embodied either (1) a personalized realistic or (2) a customized stylized self-avatar across three consecutive VR exposures in which they were accompanied by a group of virtual others being either (1) all realistic, (2) all stylized, or (3) mixed between stylized and realistic. Our results indicate groups of virtual others of higher realism, i.e., potentially more congruent with participants' real-world experiences and expectations, were considered more human-like, increasing the feeling of co-presence and the impression of interaction possibilities. (In)congruencies concerning the homogeneity of the group did not cause considerable effects. Furthermore, our results indicate that a self-avatar's congruence with the participant's real-world experiences concerning their own physical body yielded notable benefits for virtual body ownership and self-identification for realistic personalized avatars. Notably, the incongruence between a stylized self-avatar and a group of realistic virtual others resulted in diminished ratings of selflocation and self-identification. This suggests that higher-order (in)congruent visual cues that are not within the ego-central referential frame of one's (virtual) body, can have an (adverse) effect on the relationship between one's self and body. We conclude on the implications of our findings and discuss our results within current theories of VR experiences, considering (in)congruent visual cues and their impact on the perception of virtual others, self-representation, and spatial presence.